The impact of gamification on the motivation of primary schoolers under martial law - Shevchuk, Krystyna; Byhar, Hana; Pits, Iryna; Shestobuz, Olga; Dariichuk, Sergiy (Amazonia Investiga, 2023)
The purpose of this study was to identify effective interactive methods in preparing students in grades 1-4, as well as to investigate their impact on learning outcomes. The work uses theoretical and empirical methods. The analysis of existing interactive teaching methods, their selection in accordance with the age characteristics of primary school students and educational needs. Also, a pedagogical experiment was carried out based on the implementation of the developed model of using interactive teaching methods in grades 1-4 of general secondary education institutions and monitoring the learning outcomes obtained in this case. A survey of teachers and students was carried out. The study showed that the use of interactive methods in the lessons of the Ukrainian language and mathematics contributes to the growth of students' interest in studying these disciplines. As a result, there is an increase in the level of educational achievements of students from average to sufficient, and in some cases from sufficient to high. Thus, in this work it is proved that the proposed model of teaching using interactive methods that take into account the age and individual characteristics of students is highly effective. Further research should be carried out with the aim of correcting existing interactive methods in accordance with the modern educational needs of students and their individual characteristics. Research is also needed to identify new interactive methods and study their impact on learning outcomes.
Keywords: Keywords: speech skills, math skills, interactive model, academic achievements, educational needs